2009
DOI: 10.1016/j.brainres.2009.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of transgenic mice with neuron-specific expression of soluble epoxide hydrolase

Abstract: Soluble epoxide hydrolase (sEH) is the major enzyme responsible for the metabolism and inactivation of epoxyeicosatrienoic acids (EETs). EETs are produced by the cytochrome P450 (CYP) epoxygenase pathway of arachidonic acid (AA) metabolism and tend to be anti-hypertensive, anti-inflammatory and protective against ischemic injury. Since the metabolism of EETs by sEH reduces or eliminates their bioactivity, inhibition of sEH has become a therapeutic strategy for hypertension and inflammation. sEH is found in nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…However, it was found that the mechanism of protection by AUDA-BE was not due to vascular effects that would be characteristic of arachidonic acid-derived EETs or altered ischemic severity, as determined by blood flow rates. This suggests an alternate mechanism for the protection by AUDA-BE and is in agreement with the findings of another recent study demonstrating that in transgenic mice with neuronspecific overexpression of soluble epoxide hydrolase there was no change in arterial blood pressure (Bianco et al, 2009). Given that AUDA inhibits epoxide hydrolasemediated metabolism of 5,6-EET-EA (Snider et al, 2009), it is possible that the observed protective mechanism of AUDA-BE in ischemic stroke may in part be due to prolongation of the action of endogenous 5,6-EET-EA at the CB2 receptor on microglia and/or infiltrating lymphocytes.…”
Section: F Potential Involvement Of Cytochrome P450-mediated Anandamsupporting
confidence: 92%
“…However, it was found that the mechanism of protection by AUDA-BE was not due to vascular effects that would be characteristic of arachidonic acid-derived EETs or altered ischemic severity, as determined by blood flow rates. This suggests an alternate mechanism for the protection by AUDA-BE and is in agreement with the findings of another recent study demonstrating that in transgenic mice with neuronspecific overexpression of soluble epoxide hydrolase there was no change in arterial blood pressure (Bianco et al, 2009). Given that AUDA inhibits epoxide hydrolasemediated metabolism of 5,6-EET-EA (Snider et al, 2009), it is possible that the observed protective mechanism of AUDA-BE in ischemic stroke may in part be due to prolongation of the action of endogenous 5,6-EET-EA at the CB2 receptor on microglia and/or infiltrating lymphocytes.…”
Section: F Potential Involvement Of Cytochrome P450-mediated Anandamsupporting
confidence: 92%
“…75 In contrast, neuronal specific expression of sEH to increase activity 3-fold failed to increase arterial blood pressure in mice. 76 Sex differences have also been found with regards to blood pressure regulation. Basal blood pressure in Ephx2 -/- mice was lower in males but not females when compared to wild-type mice.…”
Section: Perspectivesmentioning
confidence: 98%
“…The enzyme is widely distributed in human tissues, with the largest amounts in liver, kidney, intestine, and the vasculature. sEH also is present in brain, and while it is expressed in some neurons, it is contained mostly in cortical and hippocampal astrocytes [4042]. sEH functions as a 120 kDa homodimer, and dimerization is required for enzymatic activity [43].…”
Section: Metabolism Of Pufa Epoxidesmentioning
confidence: 99%